A discrete version of the Mishou theorem related to periodic zeta-functions - Balčiūnas, Aidas; Jasas, Mindaugas; Rimkevičienė, Audronė (Mathematical Modelling and Analysis, 2024)
In the paper, we consider simultaneous approximation of a pair of analytic functions by discrete shifts and of the absolutely convergent Dirichlet series connected to the periodic zeta-function with multiplicative sequence a, and the periodic Hurwitz zeta-function, respectively. We suppose that and as and the set is linearly independent over